(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Military terminology plays a crucial role in the effective communication and coordination within the armed forces. Understanding the lexical and semantic characteristics of these terms is imperative for both military personnel and linguists. This article aims to shed light on the complexities and nuances involved in the lexical-semantic analysis of military terms.